Nursing's performance in assisting schizophrenia patients in the family environment (Research, Society and Development, 2021)
It is understood that mental health nowadays is no longer seen as it used to be, especially with the arrival of the Psychiatric Reform containing several devices to work with patients with mental disorders. Thus, the professional assistance of nurses given to schizophrenic patients is essential to assist them, becoming a link between them, the professionals of the health team and their families. The general objective of this study is to know how the provision of nursing assistance in the care of schizophrenic people can contribute to the relationship with the family during the treatment process. The methodology used in this research was a systematic review of the literature and for that purpose electronic databases Lilacs, Medline, Scielo and Google Scholar were used. Articles published between 2012 and 2020 were chosen and 10 articles were selected. The study made it possible to identify the role of the nursing team in the relationship with relatives of people with Schizophrenia, highlighting the nurse's role in raising family awareness about the treatment of patients with this mental illness. Guide families to receive and care for the mentally will in the family environment, demonstrating a relationship of trust, interpersonal relationship and psychosocial rehabilitation. It is concluded, then, that the nurse's approach to patients with schizophrenia and their families is an essential part in the monitoring and treatment, aiming at better quality of care and has a fundamental role as a mediator. It is important to carry out new studies that can contribute to the instrumentalization and qualification of nursing care in directing care for patients affected by schizophrenia, emphasizing the importance of the therapeutic relationship between nurses, patients and family members.